Pengaruh Physical Support dan Contact Personel terhadap Citra (Image) dan Kepercayaan Pasien pada Rumah Sakit Umum Tuban - Imam Suroso (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
This research is attended to analyze: (1) influence of physical support and contact personnel toward hospital image at Public Hospital in Tuban, (2) influence of physical support and contact personnel toward patient trust at Public Hospital in Tuban, (3) influence of hospital image toward patient trust at Public Hospital in Tuban. Type Research is explanatory research or confirmatory research because its target explain relation of kausal between variable examination of hypothesis. Research population is consumen / patient of Tuban Hospital. Consumer taken as sampel is patient using hospital service, minimum take care of to lodge during 3 day. Research conducted by during two week with amount of sampel 120 people. Research showed that physical support and contact personnel influence toward hospital image direcfly, positively and significantly. Physical support and contact personnel showed direct influence toward the patient trust at Public Hospital in Tuban. In addition, physical support and contact personnel showed indirect, positive and significant influence toward the patient trust of patient through hospital image.Keywords: Physical Support, Contact Personnel, Hospital Image, Patient Trust at Public Hospital in Tuban